2016
DOI: 10.1007/s10482-016-0711-8
|View full text |Cite
|
Sign up to set email alerts
|

Nocardioides pakistanensis sp. nov., isolated from a hot water spring of Tatta Pani in Pakistan

Abstract: A Gram-staining positive, non-spore forming, non-pigmented and non-motile bacterium, designated as NCCP-1340(T), was isolated from a hot water spring, Tatta Pani, Pakistan. Cells of strain NCCP-1340(T) were observed to be aerobic, rod shaped, catalase and urease positive but H2S production and oxidase negative. Growth was observed at pH 6.0-8.0 (optimum pH 7.0) and at 20-40 °C (optimum 37 °C). The strain could tolerate 0-8 % NaCl (optimum 2 %, w/v). Phylogenetic analysis based on 16S rRNA gene sequence compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…We isolated a MY-TP24 strain as a potential novel candidate species showing close branching with uncultured bacteria. Previously, Amin et al reported a novel species from the Tatta Pani hot springs (Amin et al, 2016). Together, these findings suggest unexplored diversity of novel bacteria in the Tatta Pani hot spring.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We isolated a MY-TP24 strain as a potential novel candidate species showing close branching with uncultured bacteria. Previously, Amin et al reported a novel species from the Tatta Pani hot springs (Amin et al, 2016). Together, these findings suggest unexplored diversity of novel bacteria in the Tatta Pani hot spring.…”
Section: Discussionmentioning
confidence: 72%
“…This heated water rises to the surface and mixes with shallow, non-thermal groundwater to form a hot stream (Anees, Shah & Qureshi, 2015;Baioumy et al, 2015). Studies reported thermophilic bacteria from Tatta Pani hot spring used mainly culture-dependent approaches (Amin et al, 2016;Jadoon et al, 2014;Javed et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that B. amyloliquefaciens AK9 can be used in bioconversion of lignocellulosic biomass to fermentable sugar ( Amin et al 2016a , Amin et al 2016b , Zahra et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Members within this genus have been isolated from various sources, such as different soil ecosystems (rhizosphere, desert, forest, farmland, etc.) [2][3][4][5], aquatic ecosystems (hot water spring and freshwater lake sediment) [6,7], plants [8][9][10], and animal faeces [11][12][13]. Some species in the genus Nocardioides such as Nocardioides sp.…”
Section: Introductionmentioning
confidence: 99%